Preparation and Evaluation of Domperidone/Î²-Cyclodextrin/Citric Acid/Mannitol Quaternary Inclusion Complex: An In Vitro Study - Ghorpade, Mr. Vishwajeet S. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study is to prepare quaternary inclusion complex (QIC) comprised of domperidone (DOM), Î²-cyclodextrin (Î²CD), citric acid (CA), and mannitol and to evaluate its efficiency to enhance the solubility and dissolution rate of DOM. Materials and Methods: The phase solubility studies were conducted in water and CA solutions (10 mM) in the presence and absence of mannitol (1%). The physical mixtures and kneaded complexes of DOM/Î²CD, DOM/Î²CD/CA, and DOM/Î²CD/CA/mannitol were prepared for comparative study. The prepared mixtures and complexes were subjected to saturation solubility study in water and dissolution studies in 0.1 N HCl and phosphate buffer (pH 6.8). They were characterized by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, differential scanning calorimetry, X-ray powder diffraction, and scanning electron microscopy. Results and Discussion: It was found that mannitol and CA showed synergistic effect on the solubilizing efficiency of Î²CD. The QIC showed maximum solubility of DOM (819.2 Â± 1.24 Î¼g/ml) as compared to other systems. The dissolution studies revealed that the QICs showed maximum percentage dissolution efficiency and lowest mean dissolution time. The physicochemical characterization suggested reduction in crystallinity of DOM due to complexation and a non-covalent interaction of mannitol with other components of QIC. Conclusion: Overall study revealed that the QIC containing CA and mannitol is a promising alternative to other multicomponent systems and suitable for preparing orodispersible or sustained release dosage form of poorly soluble weakly basic drugs.